Chalcone derivatives ameliorate lipopolysaccharide-induced acute lung injury and inflammation by targeting MD2 - Zhang, Ya-li; Zhang, Wen-xin; Yan, Jue-qian; Tang, Ye-lin; Jia, Wen-jing; Xu, Zheng-wei; Xu, Ming-jiang; Chattipakorn, Nipon; Wang, Yi; Feng, Jian-peng; Liu, Zhi-guo; Liang, Guang (Acta pharmacologica Sinica, 2022)
Acute lung injury (ALI) and its severe form acute respiratory distress syndrome (ARDS) are known as the common causes of respiratory failure in critically ill patients. Myeloid differentiation 2 (MD2), a co-receptor of toll like receptor 4 (TLR4), plays an important role in LPS-induced ALI in mice. Since MD2 inhibition by pharmacological inhibitors or gene knockout significantly attenuates ALI in animal models, MD2 has become an attractive target for the treatment of ALI. In this study we identified two chalcone-derived compounds, 7w and 7x , as new MD2 inhibitors, and investigated the therapeutic effects of 7x and 7w in LPS-induced ALI mouse model. In molecular docking analysis we found that 7w and 7x , formed pi-pi stacking interactions with Phe 151 residue of the MD2 protein. The direct binding was confirmed by surface plasmon resonance analysis (with KD value of 96.2 and 31.2 μM, respectively) and by bis-ANS displacement assay. 7w and 7x (2.5, 10 μM) also dose-dependently inhibited the interaction between lipopolysaccharide (LPS) and rhMD2 and LPS-MD2-TLR4 complex formation. In mouse peritoneal macrophages, 7w and 7x (1.25−10 μM) dose-dependently inhibited LPS-induced inflammatory responses, MAPKs (JNK, ERK and P38) phosphorylation as well as NF-κB activation. Finally, oral administration of 7w or 7x (10 mg ·kg −1 per day, for 7 days prior LPS challenge) in ALI mouse model significantly alleviated LPS-induced lung injury, pulmonary edema, lung permeability, inflammatory cells infiltration, inflammatory cytokines expression and MD2/TLR4 complex formation. In summary, we identify 7w and 7x as new MD2 inhibitors to inhibit inflammatory response both in vitro and in vivo, proving the therapeutic potential of 7w and 7x for ALI and inflammatory diseases.